ANALISIS YURIDIS PELAKSANAAN TJSL PERSEROAN DALAM BENTUK PEMBERDAYAAN MASYARAKAT DI BIDANG SOSIAL DAN LINGKUNGAN (STUDI PADA P.T KPC): Juridical Analysis Of The Implementation Of Corporate Social Responsibility (CSR) In The Form Of Community Empowerment. (Study at PT KPC) - Putra, Ghayana Aditya; Yunari, Sri Bakti (AMICUS CURIAE, 2025)
Corporate Social and Environmental Responsibility (TJSL) is an obligation that must be carried out by companies by paying attention to decency and fairness as stated in Law Number 40 of 2007 concerning Limited Liability Companies (UUPT) and PP No. 47 of 2012 concerning Social and Environmental Responsibility of Limited Liability Companies (PP TJSL-PT). This obligation also applies to PT Kaltim Prima Coal (PT KPC), which in its implementation takes the form of a community empowerment program in the social and environmental fields. Based on this, how is PT KPC's TJSL program funding compatible with East Kalimantan Regional Regulation Number 3 of 2013, and secondly regarding the integral part of the company's obligations in order to contribute to sustainable economic development and improving quality in the social and/or environmental fields. By using a normative legal research type, which is descriptive in nature using secondary data which is supported by primary data and then analyzed qualitatively to reach deductive conclusions. Based on the results of the analysis of the implementation of the Company's TJSL by PT KPC, there is a discrepancy in implementation based on East Kalimantan Regional Regulation Number 3 of 2013 and the forms of programs implemented are an integral part of the company's obligations to contribute to sustainable economic development and improving the quality of life in the social and environmental fields.